Dejavniki uspešnosti omrežja povezav med prodajalci in kupci na medorganizacijskem trgu - Konda, Iva (Naše gospodarstvo, 2010)
In addition to the dimensions of sense-making in a network of relationships and the conditions for the effectiveness of cooperation in the network of relationships, this article discusses the risks associated with the network of relationships as well as the success of the network. The discussion indicates that the network of relationships forms the social capital point of view and strategic alliances between firms as well. The study concludes that knowing the success factors of the network of relationships between buyers and sellers can be of great assistance to the management of a company when developing customer strategies as well as creating the company''s general strategy. The research confirms the importance of monitoring and analysing the company''s network of relationships with its customers.
Keywords: poslovno sodelovanje; omrežja; ponudba; kupci; trg; poslovna uspešnost